Strategi Guru Tahfidz Dalam Meningkatkan Hafalan Al-Qur’an Santri Rumah Qur’an Umar bin Khatab Bogor - Mahbengi, Maqfirah; lisnawati, Santi; Triwoelandari, Retno (Reslaj : Religion Education Social Laa Roiba Journal, 2024)
Memorizing the Qur'an is one way to maintain the purity of the Qur'an. While the Qur'an itself is the word of Allah which functions as a guide or guide for humans. To understand the contents of the contents of the Qur'an, namely by studying it such as tahsinul Qur'an (improving reading), makharijul letters (how to pronounce letters that are good and correct) interpretation (understanding the meaning) and the messenger establishes the Al-Qur'an as a way of life for Muslims To find out the Tahfizd Teacher's Strategy in Improving Santri's Al-Qur'an Memorization at the Umar bin Khatab Bogor Qur'an House, To find out the quality of students' Al-Qur'an memorization at the Umar bin Khatab Qur'an House Bogor, To find out the obstacles obstacles faced by tahfidz teachers in increasing the memorization of the Al-Qur'an Santri at the Umar bin Khatab Qur'an House, Bogor. Qualitative research method is a method that involves qualitative data such as observation, documentation, and interviews. Research results The methods used in learning the tahfidz program include: tikror and talaqqi. The strategy used when learning tahfidz at the House of Qur'an Umar bin Khatab Bogor. Therefore they can do tahfidz learning properly and correctly. From the explanation above that 80% of it has been running, we can conclude that every tahfidz learning strategy in the Islamic boarding school, Rumah Qur'an Umar Bin Khatab, Bogor, is still running. properly and correctly. Obstacles to the tahfidz teacher's efforts to improve the memorization of tahfidz students namely; the age of the students, the physical condition of the students, lack of motivation, the physical condition of the teacher, and the laziness of the tahfidz students. The solution is carried out by means; evaluate, provide continuous motivation, and provide extra supervision. Keywords: Teacher; Strategy; Qur'an memorization